The Effectiveness of Brogandi (A Combination of Broccoli and Centella Asiatica) on Cognitive Function Among Nursing Students - Istiqomah, Vinanda; Anisa Fitriana, Lisna; Darmawati, Irma (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Aims: This study aimed to evaluate the effectiveness of Brogandi, a combination of Broccoli and Centella asiatica, in improving the cognitive function of nursing students. Methods: A quasi-experimental pre- and post-test design was conducted involving 40 nursing students, who were divided into an intervention group (n = 20) and a control group (n = 20). Cognitive function was assessed using the Trail Making Test-B (TMT-B), Visual Recall, and Backward Digit Span. The intervention group received Brogandi supplementation at a dosage of 1000 mg twice daily for 14 days, while the control group did not receive any supplementation. Statistical analysis was performed to compare pre- and post-test results between the groups. Results: The intervention group exhibited significant improvements in cognitive performance across all tests compared to the control group. TMT-B and Backward Digit Span scores in the intervention group improved significantly (p < 0.001), and Visual Recall also showed a significant enhancement (p = 0.001). In contrast, the control group did not demonstrate significant changes in any cognitive test (p ≥ 0.248). Conclusion: The bioactive compounds in Brogandi —sulforaphane, asiaticoside, vitamin C, and vitamin E—are believed to contribute to its neuroprotective and neuroplasticity-enhancing effects. These findings suggest that Brogandi is a promising nutritional intervention for improving cognitive function, particularly in college students with high academic demands. Further research with larger and more diverse samples is needed to confirm these results and explore potential mechanisms.